Creating Environments for Continuous Employee Development and Learning - Nuraini Nuraini (Economics and Digital Business Review, 2024)
This study explores the role of leadership commitment, organizational culture, and learning frameworks in fostering continuous employee development. The research aims to investigate the impact of leadership styles, including transformational, servant, authentic, and distributed leadership, on creating a culture conducive to learning. Using a mixed-methods approach, data was collected through surveys and interviews from a sample of organizations across various industries. The findings indicate that leadership commitment significantly influences employees' attitudes towards learning and their propensity to engage in developmental activities. Moreover, organizational culture, characterized by openness to change, innovation orientation, and inclusivity, emerged as a key determinant of learning effectiveness and organizational performance. Additionally, the study highlights the importance of learning frameworks, such as formal training programs, mentorship, coaching, job rotations, and digital learning technologies, in facilitating skill development and knowledge acquisition among employees. The integration of gamification elements, microlearning, and virtual reality simulations further enhances the effectiveness and accessibility of learning initiatives. Overall, the research underscores the multifaceted nature of creating environments for continuous employee development and learning and provides insights into practical strategies for organizations to promote learning cultures and drive sustainable performance.